Comparing “Carbon Tax” and “Cap and Trade” as Mechanism to Reduce Emission in Indonesia - Putra, Juris Justitio Hakim; Nabilla, Nabilla; Jabanto, Fidelia Yemima (International Journal of Energy Economics and Policy, 2021)
Due to the high utilization of carbon results to environmental problems in most provinces in Indonesia, it can be concluded that Indonesia in urgently requires mechanism to solve environmental issues. Many attempts have been conducted by Government of Indonesia to solve the issues such as ratification of Kyoto Protocol and Paris Agreement, further the proposal on Nusantara Carbon Scheme (Skema Karbon Nusantara abbreviated as “SKN”). Unfortunately, the proposal has not adopted yet up to 2021. Calculating based on current situation, Indonesia’s greenhouse gas emissions are predicted to increase to 1.573 and 1.751 MtCO2e in 2030, which contrary to the commitment under Nationally Determined Contribution (NDC). There are several options of mechanism to be adopted, the most popular mechanism that deems highly effective are cap and trade as well as carbon tax. Many mechanisms adopted in different countries, it is important to assess which mechanism is more effective to be applied in Indonesia. Therefore, this research is conducted to assess difference on the effectiveness on carbon tax and cap and trade, examine current Indonesia’s stance towards the issue, and assess legal principle to be considered when applying the mechanism in Indonesia. Keywords: Carbon Tax, Cap and Trade, Indonesia JEL Classifications: K32, K34 DOI: https://doi.org/10.32479/ijeep.11375